1972
DOI: 10.1002/anie.197202911
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Opening of N‐Lithio‐2,3(cis)‐diphenylaziridine to 1,3(cis, trans)‐Diphenyl‐2‐azaallyllithium and Its Rearrangement to the trans, trans‐Form

Abstract: According to the above results the "alkene-created part" of the pyrrolidines obtained by [1,3]-anionic cycloaddi-tionr2] always has the configuration of the alkene used in the reaction, thus indicating stereospecific cis-addition of the alkenes (no alternative in the case of acenaphthylene). In the "azaallyl-created part" the phenyl residues of the pyrrolidines always have cis-configuration, thus proving that the stereospecific addition always involves the same 1,3-diphenyl-2-azaallyl anionr5'. The findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…25 We have not observed such products in our tin-derived anions. In Kauffmann's work on 1,3-diphenyl-2-azaallyllithium, similar results were obtained when the anion was generated by deprotonation.…”
Section: Scheme 19mentioning
confidence: 57%
See 1 more Smart Citation
“…25 We have not observed such products in our tin-derived anions. In Kauffmann's work on 1,3-diphenyl-2-azaallyllithium, similar results were obtained when the anion was generated by deprotonation.…”
Section: Scheme 19mentioning
confidence: 57%
“…Kauffmann had found that 2,3-diphenylaziridine, upon deprotonation, afforded 1,3-diphenyl-2-azallyllithium via a conrotatory electrocyclic ring opening, 25 but that the ring-opening of N-lithio-2-phenylaziridine 'proceeds slowly even at 65°C'; 4 no cycloadditions of the resultant anion were reported. Kauffmann had found that 2,3-diphenylaziridine, upon deprotonation, afforded 1,3-diphenyl-2-azallyllithium via a conrotatory electrocyclic ring opening, 25 but that the ring-opening of N-lithio-2-phenylaziridine 'proceeds slowly even at 65°C'; 4 no cycloadditions of the resultant anion were reported.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, when the same semistabilized 2-azaallyllithium was formed by the conrotatory ring-opening of N-lithio-2,3diphenylaziridine, the E,Z ('sickle') form of the anion could be captured in a cycloaddition, resulting in a trans-2,5-disubstituted pyrrolidine. 25 We have not observed such products in our tin-derived anions.…”
Section: Scheme 19mentioning
confidence: 57%
“…We then sought to reinvestigate Kauffmann's use of Nlithioaziridines as precursors of 2-azaallyllithiums, again with the hope of extending this chemistry to nonstabilized anions. Kauffmann had found that 2,3-diphenylaziridine, upon deprotonation, afforded 1,3-diphenyl-2-azallyllithium via a conrotatory electrocyclic ring opening, 25 but that the ring-opening of N-lithio-2-phenylaziridine 'proceeds slowly even at 65°C'; 4 no cycloadditions of the resultant anion were reported. Hoping to use intramolecular cycloadditions to extend this method to less-stabilized anions, we prepared the aziridine 40 and deprotonated it with n-BuLi (Scheme 10).…”
Section: Initial Attempts At Generating Less-stabilized 2-azaallyl Anionsmentioning
confidence: 99%
“…Aza-allyl anions, which are broadly classified into nonstabilized, semistabilized, and stabilized anions depending on the substitutions on the imine, are important intermediates in organic synthesis . The seminal observation by Kauffmann that deprotonation of benzylidineimine (obtained from benzaldehyde and benzylamine) forms the semistabilized aza-allyl anion, which reacts with stilbene to form the (3+2) cycloaddition product invigorated considerable interest to explore the reactivity of 2-aza-allyl anions (Figure ). Pearson’s group contributed extensively to the synthesis and reactivity of nonstabilized and semistabilized aza-allyl lithium anions by the tin–lithium exchange reaction of stannyl-substituted imines and widely utilized these intermediates in the total synthesis of alkaloids .…”
Section: Introductionmentioning
confidence: 99%